Revisiting a Christian View of the Common Good for Christian Higher Education. Issue 1 (15th March 2018) - Guthrie, David S.
ABSTRACT: Charles Gutenson's convicting words motivated me to attempt this essay. He writes: "If we are to engage in serious dialogue about the relationship between Christian faith and our [public] commitments, we must invest more energy in bringing Scripture to bear on them" (2011, p. 9). The common good seems a common conversation these days. To what extent do Christians have something specific to offer to this important dialog and to tangible common good efforts—particularly in the sense that their offerings spring from allegiance to the biblical narrative? Further, if it is reasonable to think of the mission of Christian colleges and educators as common good discipleship for Jesus' sake, what rhetoric may be helpful for undergirding and encouraging their work? My musings on the pages that follow represent my own ongoing journey to consider and to pursue these important questions as both task and joy.